SMC 2000 Conference Proceedings. 2000 IEEE International Conference on Systems, Man and Cybernetics. 'Cybernetics Evolving to S
DOI: 10.1109/icsmc.2000.885940
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effects of interruptions on task performance in the user interface

Abstract: As users continue offloading more control and responsibility to the computer, coordinating the asynchronous interactions between the user and computer is becoming increasingly important. Without proper coordination, an application attempting to gain the user's attention risks interrupting the user in the midst of performing another task. To justify why an application should avoid interrupting the user whenever possible, we designed an experiment measuring the disruptive effect of an interruption on a user's ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
214
5
3

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(231 citation statements)
references
References 3 publications
9
214
5
3
Order By: Relevance
“…It has been argued that, in the case of simple primary tasks, interruptions may even facilitate task performance (Speier, Vessey, & Valacich, 2003). On the other hand, as widely reported in the literature, interruptions may generate stress (Bailey, Konstan, & Carlis, 2001;Zijlstra, Roe, Leonova, & Krediet, 1999) and hinder in various ways the performance of the primary task -see for example (Franke, Daniels, & McFarlane, 2002;McFarlane & Latorella, 2002;Nagata, 2003;Speier et al, 2003). As emphasised by McFarlane and Latorella (2002) the implementation of any semiautonomous or user multitasking technology entails interrupting the user from other activities they are performing.…”
Section: Evaluating Alternative Focimentioning
confidence: 86%
“…It has been argued that, in the case of simple primary tasks, interruptions may even facilitate task performance (Speier, Vessey, & Valacich, 2003). On the other hand, as widely reported in the literature, interruptions may generate stress (Bailey, Konstan, & Carlis, 2001;Zijlstra, Roe, Leonova, & Krediet, 1999) and hinder in various ways the performance of the primary task -see for example (Franke, Daniels, & McFarlane, 2002;McFarlane & Latorella, 2002;Nagata, 2003;Speier et al, 2003). As emphasised by McFarlane and Latorella (2002) the implementation of any semiautonomous or user multitasking technology entails interrupting the user from other activities they are performing.…”
Section: Evaluating Alternative Focimentioning
confidence: 86%
“…Bailey [2] examined the COI for two interrupting tasks on six primary tasks, finding memory demand in the primary task at the point of interruption to be most predictive of COI, rather than any demand incurred by the interrupting task. Similarly, an effect of primary task workload demand was also found by Speier [25], wherein for highly-demanding primary tasks, interruptions can inhibit performance; conversely, they also found that interruptions can actually improve performance on lowdemand primary tasks, another Zeigarnik effect [32].…”
Section: Predicting the Coimentioning
confidence: 99%
“…Effects of interruptions have been studied in many naturalistic and experimental settings, resulting in implications for designing applications to support productivity [2], decision-making [25], and vigilance [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a number of research groups have presented a lot of work around interruption and recovery with the goal of having a highly efficient interrupt with low intrusion [4,7,8,12,13,14,20].…”
Section: Interruption and Feedbackmentioning
confidence: 99%
“…Instead of using a physical puppet [9], we used a plastic plant based on the Hanappa toy 4 . The original Hanappa plant, manufactured by Sega Toys, flexes its petal and/or leafs based on human's speech input.…”
Section: Physical Feedbackmentioning
confidence: 99%